Beban dan Respons Psikososial pada Pasien Diabetes Melitus - Yanti Apriyanti; Susmadi Susmadi; Riyanto Riyanto; Dwi Susilowati (Journal of Telenursing (JOTING), 2026)
This study aims to summarize scientific evidence regarding psychosocial burden, psychological responses, and coping strategies in patients with diabetes mellitus (DM) as a basis for developing a more comprehensive management approach. The research method used a literature review by examining national and international articles published in the last five years. Articles were selected based on predetermined inclusion and exclusion criteria, then analyzed narratively to identify key themes related to psychosocial aspects in DM patients. The results showed that DM patients often experience various psychosocial problems, particularly diabetes disorders, depression, anxiety, and social stigma, which impact quality of life, therapy adherence, and glycemic control. This psychosocial burden is influenced by sociodemographic factors, disease duration, complications, beliefs about treatment, social support, and access to health services. Patient responses showed diverse coping strategies, both adaptive and maladaptive. While the integration of psychosocial support, diabetes education, and family involvement has been shown to improve quality of life, treatment maintenance, and glycemic control. In conclusion, diabetes mellitus management requires a holistic approach that integrates mental health screening, psychosocial interventions, ongoing education, and family support as an integral part of diabetes management to optimize patient health.   Keywords: Diabetes Mellitus, Diabetes Distress, Coping, Mental Health, Psychosocial